Mass loading and episodic variation of molecular markers in PM2.5 aerosols over a rural area in eastern central India - Jayant Nirmalkar (2018)
© 2015 Elsevier Ltd. The impact of biomass burning in atmospheric aerosols load is poorly known. We investigated the impact of biomass burning through molecular markers on the concentration of PM < inf > 2.5 < /inf > aerosol samples collected from a rural site in eastern central India during three episodic periods from October to November 2011. The collected PM < inf > 2.5 < /inf > samples were chemically quantified for potassium as well as sugars and dicarboxylic acids using ion chromatography. Levoglucosan and glucose were found as the most abundant sugar compounds and sugar-alcohols showed the predominance of mannitol whereas oxalic acid was the most abundant diacid followed by maleic acid in PM < inf > 2.5 < /inf > aerosols. Substantially enhanced concentrations of K < sup > + < /sup > as well as levoglucosan and glucose were observed in eastern central India. Analysis of the source specific molecular markers and ratios of sugars and diacids infer that combustion of biomass was the major emission sources of organic compounds associated with PM < inf > 2.5 < /inf > aerosols over eastern central India. We applied Spearman correlation analysis and principal component analysis to further investigate the sources of measured sugars and diacids. The concentrations of K < sup > + < /sup > and levoglucosan were significantly correlated with sugars and diacids that verifying their common sources from biomass burning emission. This study demonstrates that biomass burning for domestic heating and cooking purposes and agricultural activities significantly influence the air quality of eastern central India during the investigation period. The obtained data in this research is helpful for the global scientific community to assessments and remedial of air quality parameters in rural areas of developing countries under similar atmospheric circumstances.